1983
DOI: 10.1901/jaba.1983.16-129
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Training for Siblings of Autistic Children

Abstract: The present study was conducted to investigate the effectiveness of a program designed to teach behavior modification procedures to normal siblings of autistic children. Three sibling pairs participated in a multiple-baseline analysis of the effects of training the normal siblings to use behavior modification procedures to teach their autistic brother or sister a variety of learning tasks. Results indicated that the siblings learned to use the behavioral procedures at a high level of proficiency, they used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 17 publications
2
61
0
3
Order By: Relevance
“…Overall, functional relationships were demonstrated between training of DTT procedures and student interventionist treatment adherence and between implementation of peer-mediated DTT and skill acquisition by target students. This supports the finding of Schreibman et al (1983), who found elementary-age student interventionists to implement a DTT protocol with high levels of integrity, resulting in the acquisition of target academic skills in children with ASD. The current findings expand upon previous research by providing preliminary evidence for the effectiveness of peermediated DTT within the context of the schools.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, functional relationships were demonstrated between training of DTT procedures and student interventionist treatment adherence and between implementation of peer-mediated DTT and skill acquisition by target students. This supports the finding of Schreibman et al (1983), who found elementary-age student interventionists to implement a DTT protocol with high levels of integrity, resulting in the acquisition of target academic skills in children with ASD. The current findings expand upon previous research by providing preliminary evidence for the effectiveness of peermediated DTT within the context of the schools.…”
Section: Discussionsupporting
confidence: 86%
“…Although peer-mediated interventions and the procedures of DTT are separately well established in the literature, only a single study has examined the effectiveness of a peer-mediated DTT intervention to promote skill acquisition in students with ASD. Schreibman, O'Neill, and Koegel (1983) trained typically developing siblings of students with ASD to implement a discrete trial intervention protocol with them in order to teach skills such as receptive identification, stimulus discrimination, and expressive and receptive labeling. The results demonstrated that training in DTT produced high implementation integrity and application of the DTT procedures produced considerable skill acquisition above baseline levels.…”
mentioning
confidence: 99%
“…Although three of the nondisabled siblings were able to generalize their social strategies from home settings to other places, the social behavior responses of the children with autism in the generalization settings were limited. Other studies have also found that siblings could learn social skills or behavioral modification strategies and use those skills in different settings (e.g., Celiberti & Harris, 1993;Colletti & Harris, 1977;James & Egel, 1986;Schreibman et al, 1983). Moreover, this finding is consistent with the results of previous studies, illustrating the problematic issue of the generalization of social skills for young children with autism (Strain, Danko, & Kohler, 1995).…”
Section: Research Questionsupporting
confidence: 90%
“…Isto está de acordo com os trabalhos de MATES (1990), GOLD (1993), RODRIGUE et al (1993DEWEY (2002), MINTON et al (1982), FOMBONNE et al (1997 A presença de uma criança com doença crônica na família está relacionada ao aumento de depressão e somatização nos pais, aos problemas de relacionamento com os irmãos e à sensação de sobrecarga relativa à doença; e todos esses fatores, por sua vez, são preditivos de pior prognóstico para a doença da criança afetada (DANIELS et al, 1987). A não aderência de famílias, a tratamentos de um filho com doença crônica, pode estar relacionada à ênfase que se dá à oferta de terapêuticas para a criança enferma, em detrimento das necessidades de pais e irmãos, o que é freqüente nos modelos de atendimentos atuais (SCHREIBMAN et al, 1983). Atendimentos centrados na família são importantes no tratamento de crianças com doenças crônicas.…”
Section: Do Ponto De Vista Objetivo Obtido Através De Resposta Dos Punclassified
“…Atendimentos centrados na família são importantes no tratamento de crianças com doenças crônicas. E, como os irmãos fazem parte desse contexto, eles devem ser incluídos nessas intervenções (PRIZANT et al, 1997;SHARPE;ROSSITER, 2002 (SCHREIBMAN et al, 1983).…”
Section: Do Ponto De Vista Objetivo Obtido Através De Resposta Dos Punclassified